Analisa Jenis-Jenis Kerusakan Jalan Flexible Pavement Pada Ruas Jalan Di Kota Bengkulu - Edito Dwiantoro (MAJALAH TEKNIK SIMES, 2021)
Roads are an important asset because of their enormous value and very strategic role in development, so they must be properly maintained in order to function as expected. As it ages, a pavement will experience a decrease in conditions due to continuous traffic loads and other factors such as temperature and changing weather. An indication of a deterioration in road conditions is damage to the pavement surface. For this reason, road maintenance techniques are needed so that the road is always functioning at all times. Proper maintenance will provide the desired service life. Conversely, if maintenance is not carried out properly it can cause the road to break down quickly. In this study, the authors conducted research on one of the roads in the city of Bengkulu, namely Jalan Kalimantan Merpati 17 Rawa Makmur, Bengkulu City. To identify road damage using the PCI (Pavement Condition Index) method and to determine the level and type of road damage. The method of data collection is by conducting a direct survey to the location of the study which aims to find out the initial data description of the types of damage and recording of the pavement surface which is then carried out by the researcher for the evaluation of the level of damage to the road from the first source, observed, researched, and recorded for the first time by the researcher. alone. In this study, the data to be taken are: the types of pavement surface damage that occurred, the area of damage to the point of damage, the level of damage, photos of road pavement surface damage documentation. The results of this research are the types of damage that commonly occur on the Kalimantan Merpati 17 Rawa Makmur road section in Bengkulu City are edge cracking, weathering and ravelling, potheles, bumps and evaluation. Damage to segment 1 of the road segment Kalimantan Merpati 17 Rawa Makmur Bengkulu City gave results in the form of the average PCI (Pavement Condition Index) value in segment 1 of the road segment Kalimantan Merpati 17 Rawa Makmur Bengkulu City was 78.7 with very good condition (very good) .